1996
DOI: 10.1097/00001648-199611000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Human Immunodeficiency Virus Infection and Infective Endocarditis among Injecting Drug Users

Abstract: Human immunodeficiency virus (HIV) infection and infective endocarditis are serious complications of injection drug use. To determine whether HIV infection may increase the risk of endocarditis beyond that associated with drug injection, we performed a nested case-control study among injecting drug users taking part in an ongoing cohort. We identified 26 participants with infective endocarditis between cohort enrollment (in 1988-1989) and June 1992, through reviews of medical records and death certificates. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(30 citation statements)
references
References 0 publications
1
29
0
Order By: Relevance
“…However, some studies have shown that HIV infection is an independent risk factor for IE in IV drug users. 15,16 In our study population, multivariate analysis identified the following 4 variables as being independently associated with HIV infection: more than 5 years' use of IV drugs, right-sided IE, infection not due to S viridans, and white blood cell count at admission of no more than 10 ϫ 10 9 /L. The reason for the higher predominance of tricuspid valve involvement in HIVinfected IV drug users is not known.…”
Section: Commentmentioning
confidence: 91%
“…However, some studies have shown that HIV infection is an independent risk factor for IE in IV drug users. 15,16 In our study population, multivariate analysis identified the following 4 variables as being independently associated with HIV infection: more than 5 years' use of IV drugs, right-sided IE, infection not due to S viridans, and white blood cell count at admission of no more than 10 ϫ 10 9 /L. The reason for the higher predominance of tricuspid valve involvement in HIVinfected IV drug users is not known.…”
Section: Commentmentioning
confidence: 91%
“…The OR increases to 8.31 at a CD4 + count of <350 cells/uL. [11] The mortality in patients with HIV and concomitant IE with a CD4 + count <200 cells/uL tends to be higher than in other groups. [12] More recent work, however, does not support the higher mortality in patients with low CD4 + counts.…”
Section: Discussionmentioning
confidence: 92%
“…This group has a characteristically higher co-infection with organisms not generally associated with HIV infection, in addition to "traditional" opportunistic infections (Manoff et al 1996), while presenting a comparable median survival time after AIDS diagnosis to that observed in other exposure categories. However, these individuals may not be representative of the general population of IDUs, but should be assessed as "survivors" of HIV infection, considering the higher mortality of HIV infected IDUs not diagnosed as AIDS (Stoneburner et al 1988) or IDUs in general, due to a variety of non-HIVrelated causes, e.g.…”
Section: Discussionmentioning
confidence: 92%